T Wave detection by correlation method in the ECG signal - Noohi, Mahsa; Sadr, Ali (CMBES Proceedings, 2010)
The ECG signal, among all vital signals, has attracted more attention due to its importance in diagnosing health conditions. In recent years T wave alternans (TWA) has been used to predict Sudden Cardiac death (SCD). TWA is the beat-to-beat alterations in the T wave amplitude A new method is proposed in this thesis to detect these Waves more precisely and quickly. the algorithm can also be implemented with minimum errors for high noise signals. The database used in this Thesis is MIT-BIH which is provided at Physionet website. This solution is performed on more than 60 Cases of this database. Previous methods such as slope variation method which was a spectral method were sensitive to noise and had a slow speed. Therefore could not quality as online systems. Our proposed method being fast and accurate has less error even without performing noise removal on the signal.